Determination of Employee Performance through Work Motivation with Organizational Support as a Moderating Variable - Endra Teja Kesuma; Chablullah Wibisono; Bambang Satriawan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Employee performance has become a critical concern for organizations seeking to maintain competitiveness and achieve sustainable operational outcomes. In this context, organizational support, workplace conditions, and internal employee factors play an important role in shaping motivation and performance levels within organizations. This research aimed to describe the determination of organizational culture, employee competency, employee commitment, work environment, employee work motivation, organizational support, and employee work performance through employee work motivation as an intervening variable and organizational support as a moderating variable. This research used a questionnaire from 220 respondents. Data analytics will be using SEM-PLS. The results indicate that organizational culture, employee competence, work environment, and work motivation significantly influence employee performance, while employee commitment affects performance indirectly through work motivation. Organizational culture and competence improve performance directly but do not significantly enhance motivation, whereas the work environment strengthens performance both directly and through motivation. Additionally, organizational support contributes directly to employee performance but does not moderate the relationship between motivation and performance. These findings imply that organizations should prioritize strengthening workplace conditions, developing employee competencies, and maintaining supportive organizational practices to improve performance outcomes effectively.